(3GdeONd GdEONGQj hGdVQjHj, GdeONd GdESdGej hGdeONd GdOhdjs - (3SejQ eMeO(B, (3YHO GdYRjRs ((3GdEScfOQjI(B:s (3ecJHI heWHYI GdETYGY GdafjI(B,s, 1998)
(3GdeONd GdEONGQj hGdVQjHj(B- (3GdeONd GdESdGej aj Jehjd GdJfejI(B- (3eONd GdJehjd GdOhdj ddJfejIs
Keywords: (3GdJfejI GdGbJUGOjI(B- (3GdJehjds; (3GdeGdjI GdYGeI(B- (3Gdabg GdESdGejs